A Flame-Retardant Hydrogen-Bonded Organic Framework Separator for Selective Sodium-Ion Transport toward a NaF-Rich Interphase in Sodium Metal Batteries - Ali, Muhammad; Ali, Moazzam; Hussain, Hamid; Aman, Samia; Naseer, Ufra; Mahmood, Asif; Ahsan, Muhammad Tayyab; Jiang, Yinzhu; Yousaf, Muhammad (Nano-Micro Letters, 2026)
The incessant quest for high-energy-density batteries to meet the growing demand of electrification makes high-level safety operation a critical concern. Traditional polypropylene separators, susceptible to thermal instability and sodium dendrite growth, often lead to internal short circuits and catastrophic thermal runaway. Here, a flame-retardant, dendrite-suppressing, and ion-regulating hydrogen-bonded organic framework (HOF) separator is designed by a simple and scalable strategy. The HOF lattice, featuring abundant polar N–H and C=O sites, preferentially coordinates PF6−. This selective interaction suppresses anion migration, yielding a high Na+ transference number (0.91). Concurrently, the liquid-filled pores and weakly coordinating channels of the HOF facilitate rapid Na+ transport, achieving an ionic conductivity of 1.57 mS cm−1 at 60 °C. Interfacial analyses reveal that the HOF stabilizes Na+ deposition by fostering a NaF-rich solid electrolyte interphase with a high Young’s modulus (~ 11 GPa), which suppresses dendrite penetration. Furthermore, thermogravimetric and combustion tests confirm exceptional resilience above 380 °C and the formation of carbon nitride layer that effectively suppresses heat release. Consequently, Na||Na symmetric cells cycle stably for over 2000 h at 2 mA cm−2, while Na||Na3V2(PO4)3 full cells retain high capacity ~ 99% over 5000 cycles at 5 C. A pouch cell with a Prussian blue cathode further demonstrates practical applicability with consistent operation at 0.5 C. This multifunctional HOF separator establishes a new paradigm for stable, fast, selective, dendrite-free, and fire-safe sodium metal batteries. Highlights: 1 A multifunctional melamine cyanurate hydrogen-bonded framework separator provides intrinsic flame retardancy, high-temperature dimensional stability, and dendrite suppression, offering a practical alternative to commercial polyolefin separators for sodium metal batteries. 2 Polar N–H/C=O motifs preferentially interact with PF6−, suppressing anion migration and boosting Na+ transference number, enabling uniform Na+ flux and lower polarization. 3 Separator-driven interphase regulation forms an inorganic, NaF-rich solid electrolyte interphase confirmed by X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry 3D mapping, improving Na plating/stripping reversibility and long-term full-cell durability at elevated temperature.